Old English sǣte and the historical significance of 'folk'-names - Baker, John (Wiley, 2017)
Old English sǣte names survive in documentary sources and place-names, and have been used in historical discourse as evidence for early and middle Anglo-Saxon socio-political organization. Earlier analyses, founded on incomplete datasets, have attempted to interpret the material in isolation from its onomastic context; this has led to confusion about the significance of such names. Here the analysis of sǣte names is based on a more complete corpus, leading to a radically new interpretation of their distribution, chronology and historical context, with significant implications for our understanding of the evolution of Anglo-Saxon administrative geography and the wider perception of so-called ‘folk’ names.